In vitro biomechanical comparison of various implants in Pauwels type 3 fracture neck femur - Manjhi, Birju; Goel, S. C.; Kunwar, Abhijeet; Singh, Vakil (International Journal of Research in Orthopaedics, 2020)
Background: The objective of this study was to find out the correlation among type of implant, type of fracture and quality of bone in a cadaveric model of unstable fracture neck of femur (Pauwels type 3) fixed with either; proximal femoral nail (PFN), dynamic hip screw (DHS), dynamic hip screw with an anti-rotation screw (DHS and ARS) or cannulated cancellous screws (CCS). Methods: This study was conducted on 24 cadaveric bones (6 in each group) in which unstable fracture neck of femur (Pauwels type 3) were created and fractures in each group were fixed with different implants after creating a comparable group using DEXA scan. These were tested on a cyclic physiological loading machine at 2 cycles per second with a load of 200kg. The test was observed for 10,000 loading cycles or till failure whichever occurred earlier. Subsidence was measured and analyzed. Results: Five specimens in the PFN group, 3 specimens in the DHS and ARS and DHS group completed 10,000 cycles while all the specimens in CCS group failed before 10000 cycles. Mean subsidence of the PFN group was significantly lower than the other groups. Conclusions: PFN constructs were stronger than the other constructs. However, these data must be interpreted as strictly biomechanical, representing only part of the scenario at work in vivo. Nonetheless, the significant findings of increased strength of fixation over the DHS, DHS with ARS and CCS certainly appear to support the use of PFN clinically.